Modeling of thermal load sizing for an industrial room aiming at energy efficiency - Río, Daniel Guzmán del; Silva, Henrique Almeida; Cisneros, Edry Antonio García; Torné, Israel Gondres; Neto, João Evangelista; Printes, Andre Luiz; Filho, Cláudio Duarte Silva; Cardoso, Fabio de Sousa; Sobrinho, Angilberto Muniz Ferreira (Seven Editora, 2023)
The air conditioning in environments is one of the most important points when it comes to quality in obtaining products and comfort in an industrial environment. Spaces where there is a significant amount of people require adequate air conditioning to increase the productivity and well-being of individuals, but there are also spaces that, in addition to the amount of people, house equipment and machinery, which need to be for their optimal performance with the temperature controlled. In the present work, the study and modeling of the thermal consumption of an industrial metrology room, which contains devices that need to be in spaces with a controlled temperature in order not to affect the results of the tests and calibrations of high-precision equipment, is performed by means of calculations. In the methodology developed, basic concepts of refrigeration and air conditioning were used to assist in modeling and calculating the thermal load sizing, in order to choose the characteristics and quantities of air conditioning equipment necessary to meet the space and technical requirements of the laboratory. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-174